Results of a prospective comparative open-label randomized study examining the efficacy of juice drinks fortified with prebiotic, minerals and vitamins for the nutrition of young children (phase IV) - A. I. Khavkin; T. A. Kovtun; D. V. Makarkin; G. V. Volynets; Yu. A. Koshkarova; N. A. Penkina (Лечащий Врач)
The tolerance, efficacy and safety of use in the nutrition of children from 12 to 36 months, diagnosed with acute respiratory infection, who received antibacterial therapy, were assessed, food/juice drinks enriched with prebiotic, minerals and vitamins for the nutrition of young children. The study included 60 children aged 12 to 36 months diagnosed with acute respiratory infection, who received a course of antibiotic therapy. The children of the main group (30 patients) received, after discharge from the hospital, a juicecontaining drink enriched with inulin, calcium, iron, vitamins C, E, A and D3, 130 ml once a day for 90 ± 1 day (3 months). The comparison group (control) included 30 patients who did not receive this product after discharge. Analysis of the data obtained showed that the daily use of non-adapted fermented milk products for children contributed to the prevention of dyspeptic disorders associated with the intake of antibacterial drugs, comfortable digestion, and an increase in the levels of secretory immunoglobulin A and lysozyme in the feces. Juice drinks enriched with inulin, calcium, iron, vitamins C, E, A and D3 are recommended to be included in the daily diet of healthy children over 12 months old and the diet of children over 12 months old with functional disorders of the gastrointestinal tract (constipation), used in diet therapy for prevention intestinal dysbiosis, in the daily diet of children who are often and for a long time ill, acute period of acute respiratory infections and acute respiratory viral infections, as well as at the stage of convalescence.